Potential impact of a new generation of remote monitoring platform: evaluation of the yearly triage burden for 35 595 patients. (14th October 2021) - Rosier, A; Gentils, M; Durand, J; Bensaber, A
Abstract: Background: Remote monitoring (RM) has become a new standard of care in the follow-up of patients with cardiac implantable electronic devices (CIEDs). It increases the probability of survival, reduces hospitalizations and health care costs, improves clinical outcome, prevents atrial fibrillation-related strokes and increases patient acceptance and satisfaction. However, human review of the all CIEDs generated data is tedious and time-consuming for healthcare professionals. Purpose: This study intends to determine the RM alert burden in a European multicentric cohort of patients with a CIED and the impact that a multivendor platform could have on the remote management of patients. Method: This retrospective study was conducted on all patients with a CIED remotely followed-up via a universal platform between 01/01/2020 and 12/31/2020 across 71 centers. We measured the quantity, frequency and criticality of patients' transmissions, and related episodes and alerts for all types of devices. Scheduled and triggered transmissions were included, but daily transmissions of data without alerts (such as Biotronik) were excluded as they are usually not reviewed by medical teams. Results: A total of 35 595 patients were analyzed: 12 065 (34%) implantable cardioverter-defibrillator (ICD), 8 705 (24%) cardiac resynchronization therapy defibrillator (CRT-D), 8 341 (23%) implantable pulse generator (IPG), 1 248 (4%) cardiac resynchronization therapy pacemaker (CRT-P), 1 891 (5%) subcutaneous implantable cardioverter-defibrillator (S-ICD), and 3 345 (10%) implantable loop recorder (ILR). A total of 504 580 transmissions were received, with an average of 14.2 /patient (p)/year (y). 81% of the transmissions were scheduled, 16% patient-initiated and 3% device initiated. A total of 1 521 653 episodes were received (41.5/p/y) with CRT-D (63/p/y) and ILR (54.6 y/p/y) generating most of the episodes. Most common episodes for CRT-D is AT (atrial tachycardia)/AF atrial-fibrillation) (51%), whereas AT/AF (39.1%) and Pause (50.4%) are most common for ILR. A total number of 814 777 alerts were triggered (22.9 /p/y). ILR had 273% more alerts (85.5/p/y) while S-ICD (12/p/y), IPG (13.1/p/y) and ICD (13.6/p/y) had less. 3.5% were set as red alerts, 32.3% yellow alerts, 7.5% blue alerts. 56.7% were set to "off" by the medical teams on the proprietary platform by using the notification settings, allowing for a universal custom filtering of alerts. A total number of 28 284 red alerts were triggered (0.8 / p/y), mostly by CRT-D (1.4/p/y) and ILR (1.3/p/y). Conclusion: A high number of transmissions, episodes and alerts are still generated by RM in 2020 with routine care settings, as measured with a new RM universal platform. Routine customizing settings across vendors allowed medical teams to reduce the total number of reviewed alerts by 57%. Algorithms identifying significant AF alerts, or readjudicating episodes from ICD and ILR could be important to further reduce the RM burden. FUNDunding Acknowledgement: Type of funding sources: None.